A Brief History of Education in Prisons in Armenia - TADEVOSYAN, MISHA V. (The journal of contemporary issues in business and government, 2021)
Introduction։ The right to education plays a key role in the system of formation, development and continuous activity of a citizen, as well as in the system of fundamental rights and freedoms a man and citizen. At present, in the Republic of Armenia (RA), at the level of laws and strategies, educational guarantees for persons held in penitentiary institutions have been established. Study purpose is to research up to present the historical development / history genesis of education in penitentiary institutions in the RA. Materials and methods։ The following methods were used, i.e. the study of documents related to educational programs implemented in penitentiary institutions of the RA, collection, generalization and analysis of primary statistical data. Results and Discussion. The history of education development in penitentiary institutions of the Republic of Armenia made it possible to conclude that 1)along with a decrease in the number of people in penitentiary institutions of the RA since 2000s, there has been an increase in the number of people involved in educational programs; 2) Despite the fact that non-formal education programs implemented by the state were initially initiated for minors and women, based on the dynamics of the last 5 years, it can be stated that they are becoming more common among adult men; 3) The steps taken by the state so far lead to the conclusion that there is a national mechanism for realizing the right to education of persons in penitentiary institutions.